The effect of learning culture on training transfer: empirical evidence in Spanish teachers - Gil Lopez, Alfonso Jesus (2018)
This paper first analyses the impact of the training process on training transfer and second the moderating effects of learning culture on training transfer. The research hypotheses are tested with a sample of secondary school teachers and through structural equation modelling. As a result, the study verifies the impact of the training process on training transfer. In addition, the learning culture moderates the relationship between the application of training and the transfer of training. The guidelines for human resource management are discussed.